A Comparative Analyses of "Robinson Crusoe" by Daniel Defoe and " Treasure Island" by Robert Louis Stevenson are two classic adventure novels that captivate readers with tales of survival, exploration, and the indomitable human spirit (Journal of Science-Innovative Research in Uzbekistan, 2023)
This article about the description of Daniel Defoe ‘’ Robinson Crusoe’’ and Robert Louis’s ‘’Treasure island ‘’ books . Although written in different times and contexts, both books present the theme of isolation and the lengths individuals will go to for their own self-preservation.By analyzing the similarities and differences in the themes, characterization, and narrative styles employed by Defoe and Stevenson, this comparative essay aims to highlight the enduring appeal of these timeless adventure stories and their universal messages of perseverance and survival